Middle Meningeal Artery Embolization in Chronic Subdural Hematoma: Implications of Pathophysiology in Trial Design - Moshayedi, Pouria; Liebeskind, David S. (Frontiers in Neurology, 2020)
Background. Chronic subdural hematoma (cSDH) is a debilitating condition with a high rate of recurrence after surgical evacuation. Summary. This review is focused on middle meningeal artery (MMA) embolization to treat cSDH. We discuss the underlying pathophysiology of chronic subdural hematoma and how cessation of arterial flow may resolve a venous hemorrhage. We also present the current evidence for MMA embolization and the roadmap for future trials. Conclusion. Frequent multimodal imaging and cSDH sampling would enable us to understand mechanisms of MMA embolization in cSDH treatment and therefore improve our ability to offer MMA embolization to the eligible population.